Depiction of Ghatapallava (vase with foliage) at the centre of the Pillar - Temples of India Project Team (Jio Institute, 2024)
The two pillars seen here belong to the original construction of the Suswani Mata Temple. The pillars have fluted shafts, at the centre are ghatapallava (vase with foliage) shaped components and the pillar capitals are shaped like a pot. The paint layers on the surface of the pillars make it difficult to understand the original form.